The road from ruin : a new capitalism for a big society - Bishop, Matthew, 1964- (A & C Black, 2011)
In September 2008 the Lehman Brothers bankruptcy ignited panic throughout the financial system, sparking a chain reaction that led to the worst global economic crisis since the Great Depression. Amid the carnage of bankruptcies, soaring unemployment, and millions of families losing their homes, lay the bloody corpse of a set of ideas that had underpinned the economics of the previous 30 years. Capitalism based on markets, especially financial markets, was believed to be delivering unprecedented prosperity, creating a general increase in wealth, including among the poorest people on the planet.